PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BADAN NARKOTIKA NASIONAL PROVINSI JAWA BARAT - Agusta, Rika Omala; Saragih, Romat (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2019)
An organization is synonymous with performance, which is defined as a measure of where an organization is success in achieving the target or not, in the province of West Java BNN in 2017 whose activities realized only reached 54.25%. One of the external factors that can influence is the work environment, it shows that BNN province of West Java has a working environment can create a disgruntled employee.This study was conducted to determine the effect of the work environment on employee performance. The method used in this research is quantitative. Using multiple linear regression with SPSS Ver.23 as data processing tools. From the data processing showed the physical work environment affects 33.1% and non-physical work environment has a greater influence second known 43.2% a significant impact on employee performance. It was concluded that the effect on the performance of employees in the province of West Java BNN is a non-physical work environment, because BNN itself has activities associated with various organizations outside the office.